Hypoxia-Inducible Factor (HIF) as a Target for Novel Therapies in Rheumatoid Arthritis - Hua, Susan; Dias, Thilani H. (Frontiers in Pharmacology, 2016)
Hypoxia is an important micro-environmental characteristic of rheumatoid arthritis (RA). Hypoxia-inducible factors (HIF) are key transcriptional factors that are highly expressed in RA synovium to regulate the adaptive responses to this hypoxic milieu. Accumulating evidence supports hypoxia and HIFs in regulating a number of important pathophysiological characteristics of RA, including synovial inflammation, angiogenesis and cartilage destruction. Experimental and clinical data have confirmed the upregulation of both HIF-1α and HIF-2α in RA. This review will focus on the differential expression of HIFs within the synovial joint and its functional behaviour in different cell types to regulate RA progression. Potential development of new therapeutic strategies targeting HIF-regulated pathways at sites of disease in RA will also be addressed.